Academic English for Engineers. Teacher's Book. - Miłosz-Bartczak, Joanna; Speller, John (Lodz University of Technology Press, 2017)
Academic English for Engineers is a task-based coursebook designed to develop the language and communication skill required by scientists and engineers for success at university and beyond. The programme focused on two main learning outcomes. After finishing the course, student be able to make effective presentations and produce formal technical writing related to their disciplines. Presentation and writing skills are taught in tandem through a series of carefully scaffolded tasks, which also involve reading and listening to improve all four major language areas. Students will further develop 21st century skills such as ICT literacy, problem-solving and critical thinking. Additional resources include phrasebanks and style guide, progress tests and lesson slides.
Politechnika Łódzka, Centrum Językowe
Keywords: task-based language learning; technical english; presentations; scientific writing; 21st century skills; additional resources; nauka języków oparta na zadaniach; angielski techniczny; prezentacje